19-base pair deletion polymorphism of the dihydrofolate reductase (DHFR) gene: maternal risk of Down syndrome and folate metabolism - Mendes, Cristiani Cortez; Biselli, Joice Matos; Zampieri, Bruna Lancia; Goloni-Bertollo, Eny Maria; Eberlin, Marcos Nogueira; Haddad, Renato; Riccio, Maria Francesca; Vannucchi, Hélio; Carvalho, Valdemir Melechco; Pavarino-Bertelli, Érika Cristina (São Paulo Medical Journal, 2010)
CONTEXT AND OBJECTIVE: Polymorphisms in genes involved in folate metabolism may modulate the maternal risk of Down syndrome (DS). This study evaluated the influence of a 19-base pair (bp) deletion polymorphism in intron-1 of the dihydrofolate reductase (DHFR) gene on the maternal risk of DS, and investigated the association between this polymorphism and variations in the concentrations of serum folate and plasma homocysteine (Hcy) and plasma methylmalonic acid (MMA). DESIGN AND SETTING: Analytical cross-sectional study carried out at Faculdade de Medicina de São José do Rio Preto (Famerp). METHODS: 105 mothers of individuals with free trisomy of chromosome 21, and 184 control mothers were evaluated. Molecular analysis on the polymorphism was performed using the polymerase chain reaction (PCR) through differences in the sizes of fragments. Folate was quantified by means of chemiluminescence, and Hcy and MMA by means of liquid chromatography and sequential mass spectrometry. RESULTS: There was no difference between the groups in relation to allele and genotype frequencies (P = 0.44; P = 0.69, respectively). The folate, Hcy and MMA concentrations did not differ significantly between the groups, in relation to genotypes (P > 0.05). CONCLUSIONS: The 19-bp deletion polymorphism of DHFR gene was not a maternal risk factor for DS and was not related to variations in the concentrations of serum folate and plasma Hcy and MMA in the study population.